INFORMATION RESOURCES OF THE CORPORATE BUSINESS SECURITY SYSTEM - POTAPOVA, Nataliya; BUSHOVSKA, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study revealed the relevance of the issue of managing corporate business security, namely from the standpoint of forming information and analytical support for the management of these processes. The research method was the improvement of the formation of theoretical-methodical and applied principles using information resources of the system for ensuring corporate business security. It has been proven that information resources provide a number of important functions and tasks in the management system of corporate business security. In general, the system of such support is formed in the following directions: (1) analysis of the business security system; (2) identification of risks and threats from the external business environment; (3) identification of internal risks and threats; (4) management and protection of information, ensuring information security; (5) business intelligence and countering economic espionage. It was concluded that for each of the identified areas, appropriate information is needed, which corresponds to the following nature of the need. Thus, within the framework of the analysis of the business security system, information is needed that includes financial and economic indicators, production indicators, labor indicators and which includes marketing aspects of the enterprise; within the scope of identification of challenges, risks and threats that come from the external business environment - analytical reviews of markets, data on competitors; reviews of the business environment, analytics, trends, expert opinions on expected changes in legislation and their consequences for business; to identify internal risks and threats - data from internal structural divisions on expected risks and threats, personnel characteristics, socionics results, reports on the rhythm of production and sales of products; within the framework of effective activity in the field of data and information protection - the level of protection of commercial information, the level of security of document circulation, the quality of information and analytical support; for the implementation of effective business intelligence - innovative and technological activities of leading competitors, objects of their intellectual property, as well as all internal information security parameters. It is argued that the collection and use of such data - information resources allows to effectively solve a whole set of tasks in the corporate security management system of business, namely, the formation of full-fledged information and analytical support for the analysis of the state, level, and structural characteristics of security; identification of existing and existing threats by directions: competitors, counterparties, decisions of authorities, factors of the external environment; temporary identification and prejudice of factors of decrease in efficiency, deliberate destructive actions of personnel, intra-company entrepreneurship, spread of low-quality, "wrong" business processes, business technologies; achieving a high level of information hygiene, cyber security, an appropriate level of information protection, preventing its leakage in any form and manifestation; Collection of the latest data for timely response to the actions of competitors, getting ahead of them by strengthening business competitiveness, protection against economic espionage.